Risk factors for renal insufficiency and survival implications after radical nephrectomy and thrombectomy in renal cell carcinoma with tumor thrombus: a systematic review - Zhigao Huang; Zhuo Liu; Lin Zhuo; Xin Ma; Zhenbin Jiang; Kewei Chen; Jiyuan Chen; Yuxuan Li; Guoliang Wang; Xiaojun Tian; Hongxian Zhang; Lei Liu; et al. (BMC Urology)
Abstract Background Renal cell carcinoma (RCC) with venous tumor thrombus (VTT) is great burden over world. Radical nephrectomy (RN) with thrombectomy seems to be its gold standard operation, which might cause reduction of renal function. The aim of this systematic review was to provide evidence about the incidence, risk factors, possible reasons and influence of renal insufficiency in RCC patients undergoing RN with thrombectomy. Methods A systematic search using PubMed, Embase, Web of Science, the Cochrane Library and European Urology databases was conducted. Study selection followed the PRISMA guidelines. After screening, eleven articles and abstracted fully compatible with the PICOS were included in this systematic review. The study was registered with PROSPERO, CRD42024516596. Results Overall, a total of 1,668 patients who were diagnosed with RCC and VTT and underwent RN (open/laparoscopic/robotic) with thrombectomy were analyzed. The postoperative renal insufficiency was present from 0.7 to 53.9%. Relevant risk factors of postoperative renal insufficiency could be summarized into three aspects: baseline characteristics (male gender, tumor thrombus level), intraoperative procedure (surgical method and inferior vena cava clamping time) and other factors (development of the times). The reason of renal insufficiency could be depletion of circulation volume, alteration in renal hemodynamics and condition of solitary kidney. The overall survival (OS) ranged from 2 months to 98 months. A clear association between survival and renal function could not be established because of the oncological risk on survival. Necessary managements like supplying blood volume, diuretic therapy and renal replacement therapy should be applied. Conclusions The present incidence of postoperative renal insufficiency was underestimated. More possible risk factors should be explored. Large cohort, multi-center, prospective, and well-designed studies would be necessary to corroborate these results and provide high-grade recommendation for clinical practice.